Mechanics of materials - Beer, Ferdinand P.; Johnston, E Russel Jr.; Dewolf, John T.; Mazurek, David F. (New York : McGraw-Hill Education, 2012)
The main objective of a basic mechanics of materials course should be to develop in the engineering student the ability to analyze a given problem in a simple and logical manner and to apply its solution a few fundamental and well-understood principles.
1) Introduction-Concept of Stress -- 2) Stress and Strain-Axial Loading -- 3) Torsion -- 4) Pure Bending -- 5) Analysis and Design of Beams for Bending -- 6) Shearing Stresses in Beams and Thin-Walled Members -- 7) Transformations of Stress and Strain -- 8) Principal Stresses Under a Given Loading -- 9) Deflection of Beams -- 10) Columns -- 11) Energy Methods.
This book provides a precise presentation of the subject illustrated with numerous engineering examples that students both understand and relate to theory and application. It explains topics ranging from detailed examples, to the homework problems, to the carefully developed solutions manual.
Keywords: STRENGTH OF MATERIALS; TECHNOLOGY